Food-Energy-Water Nexus: What would be the impact of a carbon tax? - Ringler, Claudia; Willenbockel, Dirk; Zhu, Tingju; Rosegrant, Mark (2018)
Presented by Claudia Ringler, Dirk Willenbockel, Tingju Zhu & Mark Rosegrant at Tropentag, Bonn, Sep 22, 2017.